PhilTrip : a mobile application for guiding travelers and promoting of different tourist destinations in the Philippines - Faeldonea, Ermarie Nicole L.; Lepiten, Cyril M.; Te, Charles Michael C.; Villadores, Jan Patrick A. (Manila : National University, 2017)
PhilTrip : a mobile application for guiding travelers and promoting of different tourist destinations is an online mobile based application that is designed to give Viatores the benefit of promoting their company and the Philippines in terms of tourism, and to give travellers a convenient and more unique way of sharing their travel experiences in the Philippines.
Title page -- Recommendation for oral examination -- Approval sheet/Panel of evaluators and examiners -- English Editing Certificate -- Dedication -- Acknowledgement -- Executive summary -- Publishable full paper format -- Table of contents -- List of figures -- List of tables -- Chapter I. Introduction -- Chapter II. Review of related literature and studies -- Chapter III. Technical background -- Chapter IV. Methodology, results, and discussion -- Chapter V. Summary and recommendations -- References -- Appendices.
Includes bibliographical references.